Inovasi Pelayanan Publik Berbasis Digital di Era Transformasi Birokrasi: Studi Kasus Implementasi Mal Pelayanan Publik di Kota Makassar - Mannayong, Jumalia; Natsir, Nurasia; Syafaruddin, Syafaruddin; Syafaruddin, Andi Riska Andreani (Jurnal Ragam Pengabdian, 2026)
The Public Service Mall (Mal Pelayanan Publik/MPP) is a strategic digital-based bureaucratic transformation innovation enshrined in Presidential Regulation No. 89 of 2021. Makassar City, as one of the pilot cities in Eastern Indonesia, offers a rich context for examining the dynamics of digital innovation in public services, yet in-depth academic studies on its digital innovation dimension remain scarce. This study aims to comprehensively analyze the digital innovation dimension in the implementation of Makassar City's MPP in 2025, encompassing the technology architecture employed, service digitalization processes, driving and inhibiting factors of digital innovation adoption, and its impact on public service quality and efficiency. A qualitative approach with a holistic single case study design (Yin, 2018) was employed. Data were collected through in-depth interviews with 12 purposively selected key informants, three months of participatory observation (February–April 2025), and documentary analysis. Data analysis used the interactive model of Miles, Huberman, and Saldaña (2014), with data credibility ensured through source and method triangulation and member checking. Digital innovation in Makassar City's MPP operates across four integrated layers: (1) infrastructure layer—NIK-based Single Sign-On platform connecting 22 agencies; (2) service layer—digitalization of 47 service types with measurable time standards; (3) user experience layer—iCare mobile application with real-time tracking and automatic notifications; and (4) analytics layer—data-driven performance monitoring dashboard enabling continuous service improvement. These innovations reduced average waiting time from 4.2 to 1.8 working days, raised the Community Satisfaction Index (IKM) to 84.1 by March 2025, and decreased complaint rates by 41.3% year-on-year. The success of digital innovation in MPP Makassar rests on four pillars: transformational digital leadership, human-centered technology architecture, a robust multi-actor collaboration ecosystem, and an organizational culture oriented toward continuous improvement. This model deserves to be a national reference with the necessary contextual adaptation.